Progressive tectonic evolution from crustal shortening to mid-lower crustal expansion in the southeast Tibetan Plateau: A synthesis of structural and thermochronological insights - Zhang, Guihong; Tian, Yuntao; Li, Rui; Shen, Xiaoming; Zhang, Zengjie; Sun, Xilin; Chen, Dongxu (Earth-science reviews, 2022)
Existing end-member models sparked debates concerning plateau formation in the southeast Tibetan Plateau through early-middle Cenozoic transpressional and shortening deformation or late Cenozoic regional lower crustal flow with limited crustal shortening. Therefore, the spatiotemporal pattern of deformation and exhumation is essential for distinguishing these models. Here, we present a compilation of new and previously published structural and geo-thermochronological data to explore the Cenozoic deformation history and the underpinning mechanism of the southeast Tibetan Plateau. The synthesis shows two main phases of deformation during the Cenozoic: (1) spaced late Eocene-early Miocene crustal shortening and thickening along major fault zones, including the Ailaoshan-Red River, the Xianshuihe-Xiaojiang and Yalong-Yulong faults, and (2) late Miocene deformation and exhumation that is widely distributed within and away from the major faults. Our new structural analysis in the Yuanmou area, bounded by the major fault zones, reveals an open ~N-trending antiform, named here as Yuanmou antiform, outcropping Precambrian basement in core, mantled by Mesozoic-Cenozoic strata. The youngest strata (upper Cretaceous-Paleogene) involved in the folding are unconformably overlain by undeformed late Miocene deposits, suggesting that the antiform accommodated a phase of early-middle Cenozoic ~E-W contraction, whose shortening rate is estimated as ~9%. The timing of the Cenozoic folding is quantified as ~40–28 Ma by low temperature thermochronological data. Our study shows that late Eocene-early Miocene crustal shortening and surface uplift mainly occurs along major fault zones, with limited shortening in the intervening regions. Such a shortening pattern and history suggests the formation of the regional crustal thickening and surface uplift should have occurred in the late Miocene time. Here we proposed a new progressive deformation model to explain the deformation history and the regional crustal thickening. The model infers that the spaced late Eocene-early Miocene shortening thickened the crust beneath major fault zones and progressively led to the late Miocene lateral diffusive expansion of the mid-lower crust after sufficient thermal weakening at a timescale of ~30–20 Myr. The expansion of the weakened mid-lower crust resulted in regional crustal thickening and surface uplift in the southeast Tibetan Plateau. •Structural and thermochronological data reveal limited late Eocene-early Oligocene shortening in areas between major faults.•The SE Tibetan Plateau experienced late Eocene-early Miocene spaced shortening and late Miocene distributed deformation.•Prior shortening weakened the crust and led to late Miocene mid-lower crustal expansion and regional surface uplift.